HUBUNGAN FREKUENSI SARAPAN DAN KONSUMSI JAJAN DENGAN Z-SCORE IMT/U PADA SISWA SEKOLAH DASAR - Lani, April; Margawati, Ani; Fitranti, Deny Yudi (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Background:Nutritional status is a measure of a person's body condition that can be seen from the food consumed and the use of nutrients in the body. Skipping breakfast and consuming high calorie snack foods can lead to overweight and obesity. The aim of this research was to know the correlation between frequency of breakfast and snack consumption with BMI-for-age Score in elementary school children. Confounding variables in this research are physical activity and energy intake.Method:This was an observational research with cross-sectional study design. The research was conducted in SDN Tancep 1 Gunungkidul Regency involving 67 subjects with Simple Random Sampling method. Frequency of breakfast data was obtained through interviews and was calculated based on subject’s frequency of breakfast in a week. Snack consumption and energy intake data obtained through food frequency questionnaire (FFQ). BMI-for-age score were obtained from the measurement of body weight and height, and physical activity data using physical activity record form. Data were analyzed by rank Spearman.Result:Median for frequency of breakfast was 4.00 times/week. Median for snack consumption and physical activity were 315 and 2030 kcal. The mean BMI-for-age score was -0.23±1.52. There were significant correlations between frequency of breakfast (p=0,021), snack consumption (p=0,001), physical activity (p=0,001), and energy intake (p=0,001) with BMI-for-age score. Multivariate analysis showed that 57,3% BMI-for-age score was influenced by snack consumption, physical activity, and energy intake.Conclusion: BMI-for-age score was described as 57,3% by snack consumption, physical activity, and energy intake.